A comparison between TOSCA and OpenStack HOT through cloud patterns composition. (2017) - Martino, Beniamino Di; Cretella, Giuseppina; Esposito, Antonio
Cloud computing is driving formidable change in the technology industry and transforming how enterprises do their business in Europe and around the world. However, despite its spreading, cloud computing is still affected by issues that need to be addressed carefully. Among these, challenges related to the portability and interoperability of cloud applications often arise, since there is not enough support for the development and deployment of cloud-oriented software on heterogeneous platforms and frameworks. In such a situation, cloud patterns can provide optimal solutions to several issues arising in the cloud computing scenery. However, the lack of a common standard for their representation and of tools to immediately exploit them in developing applications can hamper their usefulness. In this paper we compare two workflow description languages, namely TOSCA and OpenStack HOT, trying to assess their capability to describe cloud patterns and provide the support needed to fully exploit the solutions they provide.